Clear Cell Sarcoma of the Soft Tissue in the Distal Phalanx of the Great Toe: A Case Report - Heejun Park; Woo Young Kang; Ok Hee Woo; Aeree Kim (Journal of the Korean Society of Radiology)
Clear cell sarcoma (CCS) is a rare malignant soft tissue tumor originating from neural crest cells. Histologically resembling malignant melanoma but lacking cutaneous precursor lesions, CCS is characterized by a specific chromosomal translocation (t[12;22][q13;q12]). Primarily affecting young adults, this tumor typically arises in the extremities, especially the knee, foot, and ankle. To our knowledge, distal toe involvement is uncommon. Herein, we present a case initially diagnosed on magnetic resonance imaging as a superficial soft tissue tumor resembling malignant melanoma but subsequently confirmed as CCS of the great toe.